Perancangan Sistem Pendaftaran Audiens Seminar Proposal Di Institut Agama Islam Negeri (IAIN) Bukittinggi - Darmawan, M R; Musril, H A (Jurnal Teknologi dan Informasi (JATI), 2021)
Problems with the implementation of the proposal seminar contained in Institut Agama Islam Negeri Bukittinggi are still not effective and efficient because in processing the proposal seminar implementation data is still done manually resulting in an audience attending the proposal seminar has the opportunity to commit fraud, excessive audience numbers, and hinder the process of checking the authenticity of sign cards attending proposal seminars by students present as audiences. With these problems, the author aims to design a seminar audience registration system that can assist students in finding a proposal seminar schedule, choosing a proposal seminar schedule to be followed, printing a signed card to attend the proposal seminar, and assisting the head of the study program in managing schedule data and print audience absences. The type of research used is Research and Development (R&D in which the sequence of activities carried out systematically makes it easier to design a seminar audience registration system. With the seminar audience registration system, it makes it easy to manage the proposal seminar schedule, makes it easy to access anywhere with internet, and the implementation of proposal seminars becomes more effective and efficient because the system used is based on databases and online.